Contraception used among women of childbearing age during the pandemic COVID-19 - Estu Werdani, Kusuma; Arifah, Izzatul; Gita, Anggi Putri Aria; Rahma, Mislaillatul Khollifah; Putri, Vella Arneta; Umaroh, Ayu Khoirotul (Intelektual Pustaka Media Utama, 2024)
The low coverage of family planning acceptors during the COVID-19 pandemic became one concern of public health. This study aimed to analyze the factors related to family planning participation among women of childbearing age during the COVID-19 pandemic. This study used a quantitative research design with a cross-sectional approach. The sample size was about 373 respondents who were taken using quota sampling among women of childbearing age in Mojolaban, Sukoharjo, Indonesia. Data collection was carried out using an online structured questionnaire. The data analysis used logistic regression. There was a significant relationship between family planning status and husband's support (p-value <0.034), access to information (p-value <0.0001), and access to health services (p-value <0.0001). Multivariable analysis showed that health service access affected women's participation in family planning (OR 4.135, 95%CI 2.276-7.511). The probability of women participating using family planning was four times higher if they categorized them as having high/low health service access. Access to information is the most important factor that women of childbearing age want to use contraception during the COVID-19 pandemic. In addition, health workers need to continue to educate couples of childbearing ages about the side effects of each type of contraception so they feel safe in their use.